If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 65x = 55(x + 15) Reorder the terms: 65x = 55(15 + x) 65x = (15 * 55 + x * 55) 65x = (825 + 55x) Solving 65x = 825 + 55x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-55x' to each side of the equation. 65x + -55x = 825 + 55x + -55x Combine like terms: 65x + -55x = 10x 10x = 825 + 55x + -55x Combine like terms: 55x + -55x = 0 10x = 825 + 0 10x = 825 Divide each side by '10'. x = 82.5 Simplifying x = 82.5
| 1+8x-8x=-10 | | X/9-8=7 | | C=1+9 | | (-2)+x=0 | | -4(3n+8)=8(n+1) | | 4*(50+x)+3800*(50+2x)=6.13 | | 7(-2x+4)+6=7x-21 | | 4*(50+x)+3800*(50+2x)=6.13whatisx | | 3n+m= | | 10x+6-(3x-3)-(3x-3)= | | X=X+273 | | 5-/y-13/ | | 21b-13=29 | | 21b-13=19 | | 5(2x+6)=4(-5-2x+3x) | | 10x+5=-15 | | 1+8x-8=-10 | | 1/2(n-4)=16 | | X=2(10-x) | | 10*x=6*(3+x) | | x-37/9=7 | | 5.8-2.9-7.8= | | 4*(50+x)+3800*(50+2x)= | | 2(X+1)+2(X+1)=24whatisX | | -5(m+8)=-2(m+8) | | -4=x-3/2 | | 3-2y-1=4y-7 | | 4x-18=9x+6 | | -9(4-x)-(1+7x)=-25 | | X+3y+27=0 | | 3/4×4= | | 9+2x+14=x+17 |